Quick in situ generation of a quinone-enriched surface of N-doped carbon cloth electrodes for electric double-layer capacitors. Issue 10 (25th February 2021) - Lv, Xiaowei; Ji, Shan; Lu, Jun; Zhang, Lei; Wang, Xuyun; Wang, Hui
Abstract : A method of electro-oxidation was developed to engineer the surface features of the carbon cloth wrapped with a nitrogen-doped carbon layer, then to obtain a highly hydrophilic, carbon cloth electrode with plenty of quinone-containing sites. Abstract : Although carbon-based electric double-layer capacitors (EDLCs) have been put into practical use, their performance needs to be improved by tuning the surface features and structures of the carbon electrodes. In this study, a method of electro-oxidation was developed to engineer the surface features of the carbon cloth wrapped with a nitrogen-doped carbon layer, and then to obtain a highly hydrophilic, nitrogen-doped carbon cloth electrode with plenty of quinone-containing sites. When the obtained materials were used as electrodes in symmetric capacitors, a high area-specific capacitance (1600 mF cm −2 at 1 mA cm −2 ), high volume energy density (9.47 mW h cm −3 ), and excellent cycling stability performance (the capacitance only drops by 3% after 10 000 cycles) can be achieved. These results show that the newly developed method is an efficient approach for improving the electrochemical performance of three-dimensional carbon electrodes in EDLCs.